Clinical and Epidemiological Characterization of Patients with Herpes Simplex in Cienfuegos - Marlene Curbelo Alonso; Manuel M. Sabatés Martínez; María J. Cabrera Pereda; Eunice Díaz de Villegas Álvarez; Yoan Bernández Cruz (Medisur)
Background: Herpes simplex is a common condition, considered to be a sexually transmitted infection. Nevertheless, it is not commonly noticed. Objective: To characterize clinically and epidemiologically patients with herpes simplex virus in Cienfuegos. Methods: Prospective case series study that included 66 patients diagnosed with herpes simplex, who attended Dermatology Consultation at the Dr. Gustavo Aldereguía Lima Hospital in Cienfuegos from January to June 2007. The variables analyzed included: age, sex, skin color, family medical history, age at onset of the first injury, type of infection, location and injuries triggering factors. Results: The infection was more common in ages from 35 to 44 years old and in white skinned females. Most of them denied family medical history. The age of disease onset was after 15 years; recurrence prevailed over incidence. The mouth was the most common presentation location; stress, sun exposure and digestive disorders were found to be possible triggering factors of the disease. Conclusions: The disease appears mainly in female patients with average age of 34 years old and white skin color. Its main location was around the mouth.